Step-by-step explanation:
Y is equal to:
2/3x - 2 = 10
2/3x = 10 + 2
2/3x = 12
3/3x = (12 ÷ 2) × 3
x = 18
Not sure but its worth a try.
In the given question, we come to know that Sammy sold 5 bottles for every 3 water bottles sold by David. In this case we get the ratio as 5:3
Now this ratio indicates that the total number of bottles can be divided into 8 parts for finding out a single part. the total number of water bottles that are sold by Sammy and David together are 160.
Now on dividing this total number of bottles by 8 we get the 20 as one part.
The,
Number of Bottles sold by Sammy = 5 * 20
= 100
Number of bottles sold by David = 3 * 20
= 60
So Sammy sold 100 water bottles and David sold 60 water bottles from the total of 160 water bottles.
Answer:
ΔEFG is an isosceles triangle.
Step-by-step explanation:
Given:
E (0, 0),
F (−7, 4),
G (0, 8)
ΔEFG
Solution:
Distance formula
Distance d =
Step 1: Finding the length of EF
By using distance formula,
Step 2: Finding the length of FG
By using distance formula,
Step 2: Finding the length of GE
Thus we could see that the sides EF = FG
So it is a isosceles triangle.
Answer:
The percentage increase in bird population in the second years is 4% .
Step-by-step explanation:
Given as :
During two years, the population of birds of an island became 7 times more than before.
The the percentage increase in first year = = =40%
Let The percentage increase in second year = = r%
So, According to question
The initial population of bird = x
The increase population of bird =7 times before = 7 x
Now,
The increase population of bird = initial population of bird × (1+ ) × (1+ )
Or, 7 x = x × (1+ ) × (1+ )
Or, = 1.4 × (1+ )
Or, 7 = 1.4 × (1+ )
Or, = (1+ )
Or, 5 = (1+ )
Or, (1+ ) = 5
Or, = 5 - 1
Or, = 4
∴ r = 4 × 100
I.e r = 400
so, The percentage increase = r% = 4
Hence The percentage increase in bird population in the second years is 4% . Answer
Solve it by substitution. First let's rewrite the first equation (3x+4y=16) so we have y = something, then we'll substitue that in to the other equation.
3x+4y=16
4y=-3x+16
y=-3/4x+4
Now we can substitute this into the other equation.